PELATIHAN PENINGKATAN MUTU DAN INOVASI KEMASAN PRODUK BAKASANG DI PULAU BANDA - Sherly Lewerissa; Max R. Wenno; Adrianus O. W. Kaya; Raja B. D. Sormin; Erinn D. Noya (Pattimura University, 2026)
Bakasang is a traditional fermented fish product originating from Banda, Maluku, Indonesia, which continues to be produced using traditional methods passed down through generations. Besides serving as a local traditional food, bakasang also has significant potential as a distinctive souvenir product for tourists visiting the Banda Islands. However, the development of bakasang remains constrained by several challenges, including inconsistent product quality, limited implementation of hygiene and sanitation practices during production, and insufficient innovation in packaging and product information, which ultimately affect its competitiveness and market expansion. This community engagement program aimed to improve the quality management, hygiene practices, and packaging innovation of bakasang products through a structured mentoring approach with local producers. The program was implemented through several stages, including production condition assessment, quality control mentoring, hygiene and sanitation education, and packaging development. The results demonstrated an improvement in partners’ understanding of quality control principles, the importance of maintaining cleanliness throughout the production process, and the role of attractive packaging in enhancing product value and consumer appeal. This program is expected to contribute to the development of bakasang as a high-quality, competitive, and sustainable local food product that represents the unique culinary identity of the Banda Islands.